Elective Single Embryo Transfer: an update to UK Best Practice Guidelines. (3rd July 2015) - Harbottle, Stephen; Hughes, CIara; Cutting, Rachel; Roberts, Steve; Brison, Daniel; ,
Abstract: A significant number of multiple pregnancies and births worldwide continue to occur following treatment with Assisted Reproductive Technologies (ARTs). Whilst efforts have been made to increase the proportion of elective single embryo transfer (eSET) cycles, the multiple pregnancy rate or MPR remains at a level that most consider unacceptable given the associated clinical risks to mothers and babies, and the additional costs associated with neonatal care of premature and low birth weight babies. Northern Europe, Australia and Japan have continued to lead the way in the adoption of eSET. Randomised controlled trials or RCTs, meta-analyses and economic analyses support the implementation of an eSET policy, particularly in light of recent advances in ARTs. This paper provides a review of current evidence and an update to the eSET guidelines first published byCutting et al. (2008) intended to assist ART clinics in the implementation of an effective eSET policy.